New syllabus primary Mathematics workbook 1A - Yee, Dr Foong Pui; Hui, Chang Suo; Pearlyn, Lim Li Gek; Hua, Wong Oon (Karachi ; Oxford university press, 2019)
New Syllabus Primary Mathematics (NSPM) is a series of textbooks and workbooks specially written to reflect a student-centered approach, which serves to engage pupils so that they have a solid foundation in Mathematics.
Keywords: Mathematics - text book; Problems - exercises